Biodiversity of the Fusarium fungi causing root rot of winter cereals in Belarus - Наталья А. Крупенько; Светлана Федоровна Буга; Александр Геннадьевич Жуковский; Ирина Николаевна Одинцова; Анна Александровна Жуковская; Татьяна Геннадьевна Пилат; Вячеслав Григорьевич Лешкевич (Вестник защиты растений, 2021)
Fusarium fungi are the main causal agents of root rot of winter cereals in Belarus. As many as 12 different species were identified, with occurrence being dependent on the cereal host species and weather conditions during the growing season. Lack of precipitation from April to July led to decreasing fungal biodiversity. Fusarium pathogen complex on wheat roots was formed by F. culmorum, F. avenaceum, F. equiseti, F. oxysporum, whereas F. equiseti and F. oxysporum prevailed on triticale and rye, and F. solani, F. avenaceum and F. equiseti dominated on barley root systems. The infestation of root with F. oxysporum increased under dry conditions. In contrast, F. culmorum was isolated from root system of wheat and triticale more frequently when rainfall was sufficient. For the first time, F. cerealis and F. tricinctum were isolated from triticale, and F. cerealis from rye only, in the Republic of Belarus.